Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Komitmen Organisasi Pada PT. Tahta Sukses Abadi Medan - Clarissa Daslim; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
PT. Tahta Sukses Abadi Medan, better known as the Brastagi Supermarket, the former Tiara Hotel. Organizational commitment is still not optimal, indicated by the presence of recapitulation data on employee attendance which is still low, the lack of employee desire to work well. An unsupportive physical work environment such as piling up files that are not neatly organized, work equipment and work equipment that are not supportive because some have been damaged. Regarding the organizational culture which has the motto of working with the nature of